ZeMYB9 regulates cyanidin synthesis by activating the expression of flavonoid 3′-hydroxylase gene in Zinnia elegans - Qian, Jieyu; Jiang, Lingli; Qing, Hongsheng; Chen, Jiahong; Wan, Ziyun; Xu, Menghan; Fu, Jianxin; Zhang, Chao (Frontiers in Plant Science, 2022)
Petal color in Zinnia elegans is characterized mainly by anthocyanin accumulation. The difference in the content of anthocyanins, especially cyanidins, affects petal coloration in Z. elegans, but the underlying regulatory mechanism remains elusive. Here, we report one R2R3-MYB transcription factor from subgroup 6, ZeMYB9, acting as a positive regulator of anthocyanin accumulation in Z. elegans. Up-regulated expression of ZeMYB9 and flavonoid 3′-hydroxylase gene (ZeF3'H) was detected in the cultivar with higher cyanidin content. ZeMYB9 could specifically activate the promoter of ZeF3'H, and over-expression of ZeMYB9 induces much greater anthocyanin accumulation and higher expression level of anthocyanin biosynthetic genes in both petunia and tobacco. And then, ZeMYB9 was demonstrated to interact with ZeGL3, a bHLH transcription factor belonging to Ⅲf subgroup. Promoter activity of ZeF3'H was significantly promoted by co-expressing ZeMYB9 and ZeGL3 compared with expressing ZeMYB9 alone. Moreover, transient co-expression of ZeMYB9 and ZeGL3 induced anthocyanin accumulation in tobacco leaves. Our results suggest that ZeMYB9 could enhance cyanidin synthesis and regulate petal color in Z. elegans though activating the expression of ZeF3'H, by itself or interacting with ZeGL3.